Experimental measurement for non-spherical bulk materials flow behaviour in rectangular enclosure - Anis Farhanah, Mohd Fadzir; Siti Ilyani, Rani; Gimbun, Jolius (IOP Publishing Ltd, 2019)
Dust control is a major concern in food industries since dust emission is generally unavoidable during bulk material handling. Obtaining a better understanding of the way particles are pulled away from a stream of particles and the generation of a dust cloud will assist in the design of more efficient dust control systems. In this paper, the particles- air interactions during free fall of bulk powder is reviewed. An experimental investigation was performed to elucidate the effect of conveying velocity and particle properties on velocity profiles. The Laser Doppler Anemometry (LDA) technique was employed to measure the particle velocity during free fall. Results revealed that the particle properties (particles with flaky shapes and lower bulk density) had a great influence on dust cloud generation as compared to the conveying velocity. The results presented here may facilitate the development of a quantitative tools for dust control system design that deal with a falling stream of bulk powder.